Morphosyntactic Study on English Derivational Suffixes Forming Adjectives with Reference to the Twilight - Yuni Antari, Ni Kadek; Sedeng, I Nyoman (Humanis; Vol 22 No 3 (2018), 2018)
The title of this study is “Morphosyntactic Study on English Derivational Suffixes Forming Adjectives with Reference to the Twilight”. This study discusses the combination of morphology and syntax called morphosyntax. Morphology is the study about word formation; meanwhile syntax is the study about sentence structure. This study mainly aims at finding out the derivational suffixes forming adjectives and the syntactic functions of the adjective found in the novel Twilight. The data of this study were taken from a novel entitled Twilight by Stephanie Meyer. Library research method was applied in this study in collecting data. It was done by collecting the derivational suffixes forming adjectives, copying the data, and classifying the derivational adjectives found in the novel. The collected data in this study were analyzed using descriptive qualitative method. The main theory applied in this study is the theory of Morphology and Syntax proposed by Quirk, et al (1985). The result of the analysis shows that there were derivational suffixes that can change the word class from noun and verb into adjective. There are ten suffixes found, they are suffix -ful, -able, -ish, -ous, -al, -ic, -less, -y, -ive, -ly. Meanwhile, for the syntactic functions there are two types found, they are predicative and attributive.